Transgenes is Approaches for Crop Improvement: Enhancing crop productivity through genetic modification (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Crop improvement is an activity in which useful characteristics dispersed in numerous individuals are picked and inserted together in host to produce a variety containing as many as desirable attributes as possible (10). Recognizing valuable traits and incorporating them into future generations is very important in plant breeding. Advances in biotechnology have made it possible to identify and modify genes controlling specific characteristics (52). Increasing world population and food demands require world agricultural production be increased by 50 by 2030. In the meantime, climate change and shrinking environmental resources are limiting agricultural production over the world (32). These challenges bring an urgent need to enhance crop productivity. To breed crops with increased yield and resistance to environment stresses, a pivotal consideration is how to effectively utilize genetic diversity. Traditional plant breeding uses crossing, mutagenesis and somatic hybridization for genome modification to improve crop traits. It introduces new beneficial alleles from crossable species. Traditional plant breeding is time-consuming due to crossing barriers and linkage drag and it requires several generations of breeding and selection (23).